Proceedings of the 2017 ACM International Conference on Management of Data 2017
DOI: 10.1145/3035918.3064042
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-based Optimizer for Gradient Descent Optimization

Abstract: As the use of machine learning (ML) permeates into diverse application domains, there is an urgent need to support a declarative framework for ML. Ideally, a user will specify an ML task in a high-level and easy-to-use language and the framework will invoke the appropriate algorithms and system configurations to execute it. An important observation towards designing such a framework is that many ML tasks can be expressed as mathematical optimization problems, which take a specific form. Furthermore, these opti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…However, Postgres is not as good as Spark for general purpose batch processing where parallel full scans are the key performance factor. Several studies have shown this kind of performance differences [20,34,40,53,61]. Diversity as Common Ground.…”
Section: The Dark Side Of Big Datamentioning
confidence: 97%
See 3 more Smart Citations
“…However, Postgres is not as good as Spark for general purpose batch processing where parallel full scans are the key performance factor. Several studies have shown this kind of performance differences [20,34,40,53,61]. Diversity as Common Ground.…”
Section: The Dark Side Of Big Datamentioning
confidence: 97%
“…Moreover, today's data analytics is moving beyond the limits of a single platform. For example: (i) IBM reported that North York hospital needs to process 50 diverse datasets, which run on a dozen different platforms [38]; (ii) Airlines need to analyze large datasets, which are produced by different departments, are of different data formats, and reside on multiple data sources, to produce global reports for decision makers [9]; (iii) Oil & Gas companies need to process large amounts of diverse data spanning various platforms [19,36]; (iv) Several data warehouse applications require data to be moved from a MapReduce-like system into a DBMS for further analysis [28,56]; (v) Business intelligence typically requires an analytic pipeline composed of different platforms [58]; and (vi) Using multiple platforms for machine learning improves performance significantly [20,40]. Status Quo.…”
Section: The Dark Side Of Big Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The least-squares method is sensitive to noise and suitable for relatively small samples [30,31]. Gradient descent algorithms are often used as the core methods of training algorithms in the field of machine learning, and they is commonly used to recursively approximate a minimum deviation model, such as regression and artificial neural networks [32][33][34][35][36][37]. The batch gradient descent (BGD) algorithm is a conventional method of gradient descent that is widely used in the field of machine learning [35,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%